THE ROLE OF AN ENTREPRENEURSHIP EDUCATION IN DEVELOPING STUDENT’S ENTREPRENEURIAL COMPETENCIES: A CASE STUDY OF AN ALMATY PRIVATE UNIVERSITY - Tlekeyeva, Aray (Nazarbayev University Graduate School of Education, 2021)
In the context of Kazakhstan, research studies related to the topic of entrepreneurship education mainly focus on the regulations and documents rather than grounded research on the results of made implementations. To fill this gap, the current research explores the case of seven undergraduate students enrolled in the elective course of entrepreneurship offered at one of Almaty private universities. In this case, the research applied a qualitative research method and recruited students majoring in Information System by snowball sampling. The study used online interviews as data collection tools and attempted to understand any significant change in students’ entrepreneurship skills after completing this course....
Keywords: online learning; the impact of COVID-19; entrepreneurship education; entrepreneurship competencies; Type of access: Open Access